Ozone Treatment of Grapes During Withering for Amarone Wine: A Multimodal Imaging and Spectroscopic Analysis. (18th October 2018) - Cisterna, Barbara; Boschi, Federico; Croce, Anna C.; Podda, Rachele; Zanzoni, Serena; Degl'Innocenti, Daniele; Bernardi, Paolo; Costanzo, Manuela; Marzola, Pasquina; Covi, Viviana; Tabaracci, Gabriele; Malatesta, Manuela
Abstract: The production of Amarone wine is governed by a disciplinary guideline to preserve its typical features; however, postharvest infections by the fungus Botrytis cinerea ( B. cinerea ) not only represent a phytosanitary problem but also cause a significant loss of product. In this study, we tested a treatment with mild ozoniztion on grapes for Amarone wine production during withering in the fruttaio (the environment imposed by the disciplinary guideline) and evaluated the impact on berry features by a multimodal imaging approach. The results indicate that short and repeated treatments with low O3 concentrations speed up the naturally occurring berry withering, probably inducing a reorganization of the epicuticular wax layer, and inhibit the development of B. cinerea, blocking the fungus in an intermediate vegetative stage. This pilot study will pave the way to long-term research on Amarone wine obtained from O3 -treated grapes.